The Temperature Effect on Ultrasonic-assisted of Synthesis Methyl Ferulate and Its Antiplatelet Assay - Juni Ekowati; Rian Putra Pratama; Kholis Amalia Nofianti; Nuzul Wahyuning Diyah (UNIVERSITAS SEBELAS MARET (UNS), 2019)
Ferulic acid (FA) has been reported to have antiplatelet activity through indirectly inhibiting P2Y12 receptor. In order to increase the activity of FA, by improving its lipophilicity, so that it is easier to enter the cell, synthesis methyl ferulate was conducted through Fisher esterification. Ultrasonic waves were utilized as source of energy emitted through water as the medium at two various of temperature, i.e., 55 °C and 65 °C. The purposes of this study are to produce methyl ferulate and to determine the reaction constant rate (k) and its energy activation (Ea), at temperature of 55 °C and 65 °C. Moreover, the biological activity as antiplatelet was investigated at dose 20 mg/kg BW. The antiplatelet assay was conducted by clotting time and bleeding time methods. The results were analyzed by one way ANOVA program (P<0.05). The yield of methyl ferulate are 50.3% and 67.1% at 55 °C and 65 °C, respectively. The k value at 55°C is 4x10-5 cons-1min-1, while that of at 65 °C is 9x10-5 cons-1min-1. The clotting time and bleeding time of methyl ferulate obtained were 265 sec and 175 sec, respectively. The antiplatelet activity of methyl ferulate is better than ferulic acid.